Legal Review of the Existence of the Coordinating Ministry in The Ministerial System in Post-Reform Indonesia - Aufa Dhiya Ulhaq; Muh. Ali Masnun; Carissa Akhlaq Mulia Purnomo (Universitas Negeri Surabaya, 2024)
This research is motivated by the problematic existence of the Coordinating Ministry in the post-reform Indonesian government system, especially related to the unclear regulation of the coordinating mechanism and the unclear boundaries of the formation of the Ministry. The purpose of this study is to legally analyze the existence of the Coordinating Ministry from time to time in various post-reform government cabinets and to provide recommendations regarding ideal arrangements in the future to ensure legal certainty and efficiency of the ministerial structure. The research method used is normative legal with a statutory approach, historical approach, conceptual approach, and case approach. The results of the study indicate that the existence of the Coordinating Ministry, although not explicitly regulated in the 1945 Constitution of the Republic of Indonesia, has become an integral part of the government system through state practices and derivative laws and regulations, such as Law Number 39 of 2008 and its amendments. However, in its implementation, weaknesses were found in the aspects of coordination, politicization of positions, budget waste, and inconsistency in the number of ministries that do not have normative boundaries. This study concludes that it is necessary to reorganize the coordinating ministry system, both in terms of regulations and institutional structure, by emphasizing efficiency, effectiveness, and legal certainty so that national development goals can be achieved optimally.